Interelasi Kompetensi Profesional, Multikultural, dan Efikasi Diri Konselor Sekolah - Rudi Haryadi (Prodi Bimbingan dan Konseling Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2020)
Self-efficacy is based on competencies, this expression basically exists because of many people experience. The truth of that expression should confirm scientifically, for sure. This study aims to confirm the relationship between professional competence and multicultural competencies with the self-efficacy of school counselor in Banjarmasin City. The researcher collected data from 162 school counselor in Banjarmasin city, both those working at the junior high school level and high school / vocational school using the professional competency scale (α = 0.805), multicultural scale (α = 0.889), and school counselor self-efficacy scale (α = 0.899). The results of the study suggest that there is no positive and significant correlation between professional competence and multicultural competence together with the self-efficacy of school counselor (r = 0.006; p <0.05). However, it was found that there was a positive and significant correlation between professional competencies and multicultural school counselor (r = 0.516; p <0.01). Further research needs to check again the relationship between professional and multicultural competencies with school counselor self-efficacy using a wider range and sample size.